Chitin và dẫn xuất. Vật liệu sinh học từ chitin: da nhân tạo - Phạm, Lê Dũng (2011)
Tác giả: Phạm Lê Dũng, PTS; Cao Vân Điểm; Phạm Thị Mai; Nguyễn Thị Đông; Lê Thanh Sơn; Nguyễn Kim Thanh; Võ Thị Thứ; Trịnh Bình; Nguyễn Thị Bình; Bạch Huy Anh -- Từ khóa: Chitin; Chitosan; Vật liệu sinh học; Chất dẫn xuất; Da nhân tạo